Hercules Powder Company exhibition display (circa 1940s) - Hercules Incorporated (1940)
Series of photographs depicting exhibition display panels showcasing various industrial applications of chemicals manufactured and sold by the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Corporations; Hercules Incorporated; Advertising; Advertising, Industrial; Trade shows; Insecticides; Gums and resins; Terpenes; Cellulose industry; Rubber